Implementation and evaluation of different eradication strategies for Brachyspira hyodysenteriae - Neirynck, Willem (Porcine Health Manag, 2020)
BACKGROUND: Brachyspira infections are causing major losses to the pig industry and lead to high antimicrobial use. Treatment of Brachyspira (B.) hyodysenteriae infections may be problematic due to the high level of antimicrobial resistance. The present study implemented and evaluated farm-specific eradication programmes for B. hyodysenteriae in 10 different infected pig farms in Belgium. RESULTS: Ten pig farms clinically infected with B. hyodysenteriae volunteered to implement a farm-specific eradication programme. The programme depended on the farm and management characteristics, antimicrobial susceptibility of the B. hyodysenteriae strain and the motivation of the farmer. Two farms practiced total depopulation, six farms partial depopulation and two farms antimicrobial medication without depopulation. In addition, all farms implemented biosecurity measures, and faeces samples were tested for the presence of B. hyodysenteriae at 6, 9 and 12 months after the start of the program. Single Brachyspira isolates from before and after the programme were typed using multilocus sequence typing (MLST). Eradication was successful in four farms. Two of them (farrow-to-finish and finishing herd) had applied total depopulation and respected a vacancy period of at least 3 weeks. A third farm (gilt farm) practised partial depopulation, the rooms remained empty for 28 days and changed the source of breeding gilts. The fourth farm practised partial depopulation, the stables remained empty for 3 weeks, and used antimicrobial medication. The eradication programme was not successful in six farms. Two of the latter farms only used medication without partial depopulation. Four farms practiced partial depopulation, one of them combined it with antimicrobial medication. The cleaning and disinfection procedures, rodent control, stand-empty period and/or other biosecurity measures in the six farms were not always implemented properly. In two of three farms, isolates belonging to the same MLST type were found before and after eradication. CONCLUSIONS: Total depopulation or partial depopulation combined with implementing strict biosecurity measures allowed eradication of B. hyodysenteriae from clinically infected pig farms. Programmes based on antimicrobials without depopulation or partial depopulation without strictly adhering to all suggested biosecurity measures were not successful. Stockmanship and motivation of the farmer to permanently maintain high biosecurity standards are essential for success.